2018
DOI: 10.4070/kcj.2018.0040
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Transradial and Transfemoral Percutaneous Coronary Intervention in Chinese Women Based on a Propensity Score Analysis

Abstract: Background and ObjectivesOver the past decades, transradial approach for percutaneous coronary intervention (PCI) has been increasingly adopted in clinical practice. Women represent a large population who will possibly benefit from PCI, but they are often under-represented in clinical studies. Therefore, the role of TRI in women remains to be further defined. This study sought to compare safety and efficacy for transradial intervention (TRI) and transfemoral intervention (TFI) in women undergoing PCI in China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Since then rapid advances in this technique and related devices have catapulted transradial intervention (TRI) to an internationally accepted benchmark and a clinically viable approach to PCIs [8][9][10][11]. A series of studies have demonstrated the superiority of TRI compared to conventional transfemoral intervention (TFI) in terms of reduced risk of adverse outcomes and shorter lengths of hos-pital stays [12][13][14][15][16][17][18][19][20][21][22][23]. A recent Scientific Statement from the American Heart Association highlights these advantages and recommends TRI even in patients with acute coronary syndrome (ACS) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Since then rapid advances in this technique and related devices have catapulted transradial intervention (TRI) to an internationally accepted benchmark and a clinically viable approach to PCIs [8][9][10][11]. A series of studies have demonstrated the superiority of TRI compared to conventional transfemoral intervention (TFI) in terms of reduced risk of adverse outcomes and shorter lengths of hos-pital stays [12][13][14][15][16][17][18][19][20][21][22][23]. A recent Scientific Statement from the American Heart Association highlights these advantages and recommends TRI even in patients with acute coronary syndrome (ACS) [24].…”
Section: Introductionmentioning
confidence: 99%
“… 3) 4) 5) Furthermore, the radial approach is technically more difficult in women than in men because of their smaller-caliber radial artery and higher risk of radial artery spasm. In this issue of the Korean Circulation Journal , 6) the investigators compared the safety and efficacy of transradial and transfemoral PCI in Chinese women. In 899 propensity score-matched patients, transradial PCI was associated with reduced major post-PCI bleeding (odds ratio [OR], 0.64; 95% confidence interval [CI], 0.54–0.76; p<0.001) and access site complications (OR, 0.67; 95% CI, 0.61–0.74; p<0.001).…”
mentioning
confidence: 99%